Frequencies of activated T cell populations increase in breast milk of HCMV-seropositive mothers during local HCMV reactivation - Lazar, Katrin; Pawelec, Graham; Goelz, Rangmar; Hamprecht, Klaus; Wistuba-Hamprecht, Kilian (Frontiers in Immunology, 2024)
Background: Human cytomegalovirus (HCMV) can reactivate in the mammary gland during lactation and is shed into breast milk of nearly every HCMV-IgG-seropositive mother. Dynamics of breast milk leukocytes during lactation, as well as blood leukocytes and the comparison between both in the context of HCMV reactivation is not well understood.Methods: Here, we present the BlooMil study that aimed at comparing changes of immune cells in blood and breast milk from HCMV-seropositive-vs -seronegative mothers, collected at four time ranges up to two months post-partum. Viral load was monitored by qPCR and nested PCR. Multiparameter flow cytometry was used to identify leukocyte subsets.Results: CD3 + T cell frequencies were found to increase rapidly in HCMV-seropositive mothers' milk, while they remained unchanged in matched blood samples, and in both blood and breast milk of HCMV-seronegatives. The activation marker HLA-DR was more strongly expressed on CD4 + and CD8 + T cells in all breast milk samples than matched blood samples, but HCMV-seropositive mothers displayed a significant increase of HLA-DR + CD4 + and HLA-DR + CD8 + T cells during lactation. The CD4 + /CD8 + T cell ratio was lower in breast milk of HCMV-seropositive mothers than in the blood. HCMV-specific CD8 + T cell frequencies (recognizing pp65 or IE1) were elevated in breast milk relative to blood, which might be due to clonal expansion of these cells during local HCMV reactivation. Breast milk contained very low frequencies of naïve T cells with no significant differences depending on serostatus.Conclusions: Taken together, we conclude that the distribution of breast milk leukocyte populations is different from blood leukocytes and may contribute to the decrease of breast milk viral load in the late phase of HCMV reactivation in the mammary gland.